Prognostic factors for perioperative pulmonary events among patients undergoing upper abdominal surgery - Sakai, Rafael Luis; Abrão, Graciela Maria Gera; Ayres, José Franscisco Vasques; Vianna, Pedro Thadeu Galvão; Carvalho, Lídia Raquel de; Castiglia, Yara Marcondes Machado (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: The signifi cant relationship between upper abdominal surgery and early (perioperative) pulmonary events was investigated among patients with preoperative pulmonary conditions undergoing general anesthesia. DESIGN AND SETTING: Retrospective study for which data were obtained prospectively from 1999 to 2004, at a tertiary university hospital. METHODS: We retrospectively studied 3107 patients over 11 years old presenting American Society of Anesthesiologists (ASA) status I, II or III who underwent upper abdominal surgery under general anesthesia and were discharged to the recovery room. The preoperative conditions analyzed using logistic regression were: age, sex, ASA physical status, congestive heart failure, asthma, chronic obstructive pulmonary disease (COPD), respiratory failure and smoking. The outcomes or dependent variables included intraoperative and postoperative events: bronchospasm, hypoxemia, hypercapnia, prolonged intubation and airway secretion. RESULTS: Among these patients (1500 males, 1607 females, mean age 48 years, 1088 ASA I, 1402 ASA II and 617 ASA III), there were 80 congestive heart failures, 82 asthmatics, 122 with COPD, 21 respiratory failures and 428 smokers. Logistic regression analysis showed that female sex (p < 0.001), age over 70 years (p < 0.01), smoking (p < 0.001) and COPD (p < 0.02) signifi cantly infl uenced pulmonary event development, particularly hypoxemia and bronchospasm, at both times but not in the same patients. Asthma and congestive heart failure cases did not present pulmonary events in the recovery room. CONCLUSION: In upper abdominal surgery under general anesthesia, female sex, age over 70, smoking and COPD were independent risk factors for intra and postoperative pulmonary events.